PENGARUH 6, 8 DAN 10 KALI PEMAKAIAN MINYAK JELANTAH TERHADAP RENDEMEN HASIL REAKSI TRANSESTERIFIKASI MENGGUNAKAN KATALIS BASA HOMOGEN NaOH - Amirul Mukminin; Debora Ariyani; Eka Megawati; Yuniarti Yuniarti (Jurnal Inovasi Pendidikan dan Sains, 2023)
Research has been carried out on the effect of using used cooking oil 6, 8 and 10 times usage on the % yield of methyl ester formation (biodiesel) using a homogeneous base catalyst of 0.6% mass NaOH. All used cooking oil samples were reacted with methanol with a reactant ratio of 1:5 % by mass. The transesterification reaction of each sample was carried out at 60°C for 40 minutes. The yield of used cooking oil samples for 6 times of use was 96.6%, while 8 and 10 times of use showed values ​​that were not much different, 96.4 and 96% by mass, respectively. Gas Chromatography (GC) and Mass Spectrocopy (MS) detected 14 peaks of the compound and that the 3 highest peaks indicated that the sample contained a methyl ester. Each peak of line 4 is methyl palmitate (C17H34O2) with an area of ​​36.66%, peak of line 6 is methyl oleate (C19H36O2), area of ​​55.7% and retention time of 17.92 minutes; the peak of line 7 is methyl nonadecanoate (C20H40O2) with an area of ​​4.41% and a retention time of 18.093 minutes.